PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN - Fadillah, Adil; Koyum, Koyum (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
The main purpose of the research is to measure how big the influence of product quality and brand image on customer loyality for Starbucks. The variable that researcher used on this research are independent variable which is product quality that consist of Performance, feature, reliability, conformance, durability, ability, esthetic and fit and finish while Brand image consist of power, uniqueness and favorable. For attached variable are customer loyality. Analytical method that researcher used are SPSS version 20 with the quisioner spread of 100 respondent at Starbucks Mall Botani Square Bogor. The result of the research shown that product quality and brand image significantly influenced customer loyalty. Key Word: Product Quality, Brand Image, Customers loyalty.